Global Politics and Its Violent Care for Indigeneity - Lindroth, Marjo. author. aut Link
VIII, 152 p.
Keywords: This book challenges the common perception that global politics is making progress on indigenous issues and argues that the current global care for indigeneity is, in effect, violent in nature. Examining the inclusion of indigenous peoples in the United Nations Permanent Forum on Indigenous Issues and the Arctic Council, the authors demonstrate how seemingly benevolent practices of international political and legal recognition are tantamount to colonialism, the historical wrong they purport to redress. By unveiling the ways in which contemporary neoliberal politics commissions a certain type of indigenous subject—one distinguished by resilience in particular—the book offers a pioneering account of how international politics has tightened its grip on indigeneity.